Discovering teacher trainees teaching preferences using metaphors - Awang Rahmat, Dayangku Ziela Natasha (Universiti Malaysia Sarawak (UNIMAS), 2009)
Metaphor can be a way to reflect our belief about ourselves, others and the world in another perspective. From metaphor, variety of evaluations can be made. By analyzing metaphor generated by teachers, teaching preferences can be predicted where the teaching and learning in the language classroom can be enhanced (Nikitina & Furuoka, 2008). This study examined the images UNIMAS teacher trainees have about the training that they received to be an English language teacher and as a result the teacher trainees preferred teaching methods were predicted. The study involved 61 participants from TESL programme and 14 participants from ESL programme. The instruments used for data collection was a photocopied form with an incomplete sentence “Training to be an English language teacher is like …”. The data were analysed using the typology of metaphors developed by Oxford et al. (1998). Results showed that majority of the metaphors reflected the Learner-Centered Growth perspective. Based on this, it was predicted that the teacher trainees preferred teaching methods were the Silent Way, Community Language Learning and the Communicative approach. In relation to this, the findings also seem to suggest there have a realization of the importance of the learner-centered growth in maximizing the inner potential of the language learners.